2015
DOI: 10.4085/1062-6050-49.3.82
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Light Therapy to Attenuate Strength Loss After Strenuous Resistance Exercise

Abstract: Context: Near-infrared (NIR) light therapy is purported to act as an ergogenic aid by enhancing the contractile function of skeletal muscle. Improving muscle function is a new avenue for research in the area of laser therapy; however, very few researchers have examined the ergogenic effects of NIR light therapy and the influence it may have on the recovery process during rehabilitation.Objective: To evaluate the ergogenic effect of NIR light therapy on skeletal muscle function.Design: Crossover study. Main Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The ''pulsing'' of the low-powered pulsed laser/light device and the low power of the low-powered continuous laser/light device may explain the superior results compared with the high-powered continuous laser/light treatment, because both devices generate only a small amount of superficial heat. 21,22 The MVC results of the high-powered continuous laser/ light group are similar to those of Larkin-Kaiser et al, 28 who applied 360 J using a high-powered laser and demonstrated a small, nonsignificant difference between placebo and the active groups at 24 hours and no difference at 48 hours after the treatment. However, we delivered nearly 50% of that dose and found similar reductions in MVC, which were not reversed during the course of the study.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The ''pulsing'' of the low-powered pulsed laser/light device and the low power of the low-powered continuous laser/light device may explain the superior results compared with the high-powered continuous laser/light treatment, because both devices generate only a small amount of superficial heat. 21,22 The MVC results of the high-powered continuous laser/ light group are similar to those of Larkin-Kaiser et al, 28 who applied 360 J using a high-powered laser and demonstrated a small, nonsignificant difference between placebo and the active groups at 24 hours and no difference at 48 hours after the treatment. However, we delivered nearly 50% of that dose and found similar reductions in MVC, which were not reversed during the course of the study.…”
Section: Discussionsupporting
confidence: 72%
“…These participants fatigued faster than those in the other groups, which may have caused the muscles to work harder and experience catabolic effects. No participants dropped out of our study, but Larkin-Kaiser et al 28 had 1 participant drop out because of excessive arm pain. This corresponds with our finding that the high-powered continuous laser/light treatment did not improve muscle performance or modulate the pain associated with DOMS.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… Photobiomodulation Freire et al [ 85 ] No info Source, laser (GaInPAl; 660 nm) and LED (670 nm); wavelength, 660 and 670 nm; power, 40 mW (laser), 150 mW (LED); frequency, CW; beam area, 4 mm 2 (laser) and 0.5 cm 2 (LED) Irradiance, –; time, 30 s (laser) and 16 s (LED); energy, 16 J; radiant exposure, 4.8 J/cm 2 (laser) and 4 J/cm 2 (LED) The best results were obtained from the preventive laser and LED photobiomodulation groups; both groups were effective in diminishing the oral mucositis lesions. Larkin-Kaiser et al [ 89 ] No info Source, laser; wavelength, 800 and 970 nm; power, 3 W; frequency, –; beam area, – Irradiance, –; time, 4 min; energy, 360 J; radiant exposure, – Applied to skeletal muscle before resistance exercise, NIR light therapy effectively attenuated strength loss. de Carvalho et al [ 90 ] No info Source, GaAlAs (660 nm, laser) and InGaAlP (630 nm, LED); wavelength, 660 and 630 nm; power, 40 mW (laser) and 150 mW (LED); frequency, CW; beam area, 4 mm 2 (laser) and 0.8 cm (LED) spot Irradiance, –; time, –; energy, –; radiant exposure, 4.8 J/cm 2 Laser and LED photobiomodulation were effective in accelerating the healing of formocresol-induced oral ulcers in both clinical and histological aspects.…”
Section: Resultsmentioning
confidence: 99%
“…Further to improving skeletal muscle regeneration, a growing body of studies has been demonstrating positive effects of LLLT applied prior and post exercise sessions related to muscle recovery [18][19][20][21]. Further, a previous study evaluated the effect of chronic aerobic exercise practice and LLLT interaction applied post a musculoskeletal atrophy model, verifying that the interaction with exercise and LLLT was effective in preventing the muscle atrophy [22].…”
Section: Introductionmentioning
confidence: 99%